HUMAN RESOURCE MANAGEMENT AND ARTIFICIAL INTELLIGENCE automating and Optimizing Processes. - Agrawal, Vidhi (Routledge Research in Human Resource Management., 2025)
This edited volume undertakes an intellectual expedition aimed at elucidating the symbiotic relationship between Artificial Intelligence (AI) and the domain of Human Resource Management (HRM). Aligned with a forward-looking perspective, this scholarly work embarks on a comprehensive inquiry into the transformative capacities of AI within distinct HR functions, including but not limited to recruitment, performance evaluation, and employee development. As organizations embrace the transformative potential of AI, the book unfurls a roadmap that navigates the complexities of this transition. Insights into the metamorphosis of HRM practices, the recalibration of workforce dynamics, and the resultant organizational culture metamorphosis provide prescient guidance for stakeholders navigating the uncharted waters of AI adoption. Its overarching framework aspires to cultivate an environment conducive to intellectual discourse, offering a collaborative platform for academic scholars, research practitioners, industry experts, and policymakers to engage in the nuanced exploration of emergent AI-driven paradigms in HRM, organizational culture, and management of technology and innovation.